RISK MANAGEMENT IN ISLAMIC BANKING: PRINCIPLES, PRACTICES, AND CHALLENGES - Safarova Nasiba Gulmurod kizi (Innovation Science and Technology, 2025)
This article explores the principles, practices, and challenges associated with risk management in Islamic banking. With the rising prominence of Islamic finance globally, particularly in countries with large Muslim populations, it is crucial to understand the unique aspects of risk management that differentiate Islamic banking from conventional banking systems. The study focuses on key Islamic finance principles such as the prohibition of interest (riba), risksharing, and ethical investment, which influence the way risks are identified, assessed, and managed. By conducting a comprehensive review of existing literature and analyzing current practices, this paper provides a detailed overview of the risk management framework in Islamic banks, highlighting both the advantages and challenges inherent in these systems.